THE INFLUENCE OF MOTIVATION AND MINIMAL CAPITAL ON STUDENTS' INTEREST IN INVESTING IN THE ISLAMIC CAPITAL MARKET AT THE EX-RESIDENCE OF PATI - Septiana Wurianti; Susi Susanti; Ahmad Taufik Hidayat; Ibnu Muttaqin (AT-TIJARAH: Jurnal Penelitian Keuangan dan Perbankan Syariah, 2023)
The desire to invest in Indonesian society including student is still very low, especially investment in the capital market. This is because of the views of the community and students who think that invesment contains risks and requires a lot of capital. In this reseacrh, the purpose to do knowing the effect of motivation and minimal capital on investment interest in the capital market in Pati Ex-residency students. The population in this research were students of the former residency of starch which included STAI Pati, IPMAFA, IAIN Kudus, University of Muria Kudus, STIKES BAKTI UTAMA, and UNISNU Jepara with a total sample of 102 students. Sampling method with random sampling technique. The method used to analyze the data is multiple linear regression. The results of this study indicate that motivation, minimal capital has an effect on the interest of Ex-Residency Pati students to invest in the islamic capital market.